Kebijakan Pemerintah Daerah Dalam Penanggulangan Wabah Corona Virus Diease 2019 di Kabupaten Lamongan - Fahmi Anas (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2021)
This study examines the policies of the Lamongan Regency government in preventing and overcoming the Covid-19 outbreak. Lamongan Regency Regulation No. 35 of 2020 concerning the prevention and control of Corona Virus 2019 in transition to recovery is one of the policies issued by the Lamongan Regency Government. This research aims to implement prevention and recovery policies in overcoming the Covid-19 outbreak in Lamongan Regency. The research method used is descriptive qualitative. The use of a qualitative approach in this research is descriptive analysis, the researcher wants to describe the policy of controlling and preventing Covid-19 in the transition to recovery in Lamongan Regency This research uses data sources from scientific journals, literature books, official websites which then come from descriptive analysis of prevention policies, and recovery in the response to the Covid-19 outbreak in Lamongan Regency. The results of the study explained that the prevention and control of the Corona Diease 2019 Virus in the transition to recovery in Lamongan Regency was the formation of a Covid-19 accelerated handling task force to accelerate the handling of Covid-19, the availability of health facilities and infrastructure for the Covid-19 test, quarantine or isolation areas, as well as massive close contact tracing. Prohibition of traveling without masks, guaranteeing goods vehicle activities and business operations (shops). The involvement of various parties has greatly helped government programs in overcoming Covid-19, such as the village head, community leaders and the interaction of the TNI and Polri which greatly helped create security and order during the prevention and recovery of Covid-19 countermeasures in Lamongan Regency.